Enhanced performance of Fe‐JUL‐15 prepared by ultrasonic method through the photo‐degradation of ibuprofen. Issue 2 (17th October 2017) - Guettaia, D.; Boudjemaa, A.; Bachari, K.; Mokhtari, M.
Abstract : The present study involves the degradation of ibuprofen (IBP) anti‐inflammatory drug used in the pharmaceutical sector by photo‐catalysis, photolysis and photo‐Fenton processes. IBP degradation through these processes was investigated under UV irradiation used a catalyst based on iron incorporated in mesoporous silica framework (JUL‐15). The catalyst was characterized by XRD, BET, FTIR, diffuse reflectance UV‐Vis, SEM/EDX, and electrical conductivity. The photo‐catalytic properties of this material were evaluated via IBP degradation by varying different parameters as the pH levels, the concentration of IBP and the catalyst amount. The IBP abatement was monitored by UV‐visible spectrophotometry and HPLC. The characterization results indicated that, the material has a small particles size and a specific surface area above 109 m 2 g −1 . The optical band gap (∼ 1.4 eV) obtained from Kubelka‐Munk equation was well suited in the UV region. A higher degradation was observed with an initial catalyst concentration of 0.25 g/L. Moreover, the catalyst demonstrates significant photo‐degradation after 210 min under UV light (lamp's wavelength of 254 nm). © 2017 American Institute of Chemical Engineers Environ Prog, 37: 738–745, 2018